Infestations of meloidogyne exigua in asian rubber clones in mato grosso, Brazil - Filho, José Carlos Pezzoni [UNESP]; Brida, Andressa Lima [UNESP]; Takata, William Hiroshi Suekane; Wilcken, Silvia Renata Siciliano [UNESP]; Furtado, Edson Luiz [UNESP] (FapUNIFESP (SciELO), 2019)
Among the phytosanitary problems of rubber tree cultivation is the incidence of root knot, more specifically Meloidogyne exigua race 3, demonstrating great importance for the crop, which was verified in the present evaluation since it led to crop abandonment. In this experiment, infestation of M. exigua was evaluated in rubber tree crop, without rootstock identification, in the roots and soil and in clones GT 1, PR 255, PB 235, PB 217 and RRIM 600; infestations were verified between clones/grafts and among the populations evaluated in two periods of 2013. The experiment was conducted in the municipality of Itiquira-MT, where samples of roots and soil were collected at each point in May and November. The nematological analysis of roots and soil was carried out according to specific methodologies. Statistical analysis was performed in a completely randomized design, with 5 x 2 factorial scheme and 15 replicates. Infestation data were transformed into log (X + 1) and subjected to analysis of variance and, when significant, means were compared according to Tukey’s test at 5% probability. The populations were high for all clones, and the infestations in the roots and soil in May were higher than those in November. The infestations of M. exigua in the roots and soil, means between data from May and November for evaluated clones/grafts, did not present significant differences according to Tukey’s test, but there was a significant difference according to the same test between the mean infestations of May and November.
Infestações de meloidogyne exigua em clones asiáticos de seringueira no mato grosso, Brasil
Keywords: Hevea brasiliensis; Lasiodiplodia theobrome; Root-knot